Analysis and Selection of Multicultural Guidance Research Instrument Scale - Aqra, Naila Rumaisha; Ahman, Ahman (Bulletin of Science Education, 2024)
This research discusses the scale analysis of multicultural guidance instruments on students at Madrasah Aliyah Al Huda Cikalongwetan. West Bandung Regency. The following are the results of the Validity Test and Reliability Test of the research instrument scale regarding multicultural counseling. This Validity Test uses Pearson Correlation to determine the extent to which each item in the measurement instrument correlates with the total score. In the table presented, 67 items (X1 to X67) were tested. The Pearson Correlation value for each item ranges from 0.738 to 0.881, indicating that each item has a strong relationship with the total score. The significance value for all items was 0.000, which is well below the significance level of 0.05. This indicates that the correlations found do not occur by chance and are highly statistically significant. Based on the validity test results, all items (X1 to X67) were declared valid. This is indicated by the high Pearson Correlation Value and the very low significance value (0.000). Thus, the measurement instrument used can be considered valid to measure the intended construct. The Reliability Test results show that the measurement instrument consisting of 67 items has a Cronbach's Alpha value of 0.991. This value is very high and close to 1, which indicates that the instrument has excellent internal consistency. In other words, the items in this instrument consistently measure the same construct, so they can be relied upon to produce stable and accurate data. This high Cronbach's Alpha value provides confidence that the instrument can be used with confidence in research to measure the variable in question Keywords: Multicultural, Multicultural Counseling, Multicultural Guidance